Analisis Tingkat Kepuasan Pasien terhadap Kualitas Pelayanan Apotek Sidowaras 1 di Ambarawa - Filda Amalia Zahrifa; Gerson Musa Puaraty; Noviana Dwi Lestari; Niken Dyahariesti (Journal of Educational Innovation and Public Health, 2026)
One key metric for evaluating the quality of pharmaceutical services provided by pharmacies is patient satisfaction. Patient trust, medication adherence, and therapeutic success can be improved with high-quality services. “Using the five characteristics of Service Quality (SERVQUAL) empathy, tangibles, responsiveness, reliability, and assurance this study sought to assess the level of patient satisfaction with the quality of pharmaceutical services at Sidowaras 1 Pharmacy in Ambarawa. This study employed a cross-sectional design and a survey method with a quantitative descriptive approach. A questionnaire that had undergone validity and reliability testing was used to collect data prospectively. This study involved 100 respondents who met the inclusion criteria. Reliability testing produced a Cronbach's Alpha score of 0.884, indicating a very high level of instrument reliability. While validity testing findings indicated that all statement items were valid with a calculated r value greater than the table r (0.361). The findings indicate that Sidowaras 1 Pharmacy's pharmaceutical services have an acceptable level of patient satisfaction. The average satisfaction scores were 58.75% for the empathy dimension, 37% for the physical dimension (very satisfied), 46% for the responsiveness dimension (satisfied), 36.5% for the reliability dimension (quite satisfied), and 43.6% for the assurance dimension. Overall, the pharmaceutical services offered have satisfied patients and met their expectations”. It is hoped that the findings of this study will be used as assessment data in initiatives to continuously improve pharmaceutical service standards.